Manajemen Mutu Terpadu Pondok Pesantren Raudlatul Muslimin NW Kayangan Batu Layar Lombok Barat - Fathurrahman Muhtar (Prodi Tadris Matematika-UIN Mataram, 2021)
This is an activity to focus on developing a madrasa community supported by UIN Mataram which is to develop Madrasah Aliyah Nahdlatul Wathan Raudlatul Muslim Kayangan Sandik's management capabilities. Coaching method for madrasah development plan with Trainer of Trainer (TOT) strategy material for five pillars of Total Quality Management (TQM). The results will provide leaders, teachers, employees and stakeholders with a clear understanding of the concept of the five TQM pillars. The understanding is then transferred into the development plan for madrasah